The role of the river, active landscape and greenery in the formation of urban development in Kyiv - Markovskyi, Andrii; Tovbych, Valerii; Lagutenko, Olga (Landscape Architecture and Art, 2021)
The article analyzes the influence of the water artery – the Dnieper River and the active relief on the specifics of the city development on the example of Kyiv since ancient times. The specifics of the development of Kiev was that this development began from the territories close to the Dnieper, located on the right steep bank of the city. It is proved that initially the maximum use of proximity to the river and active Landforms was applied exclusively for religious dominants, whereas since the Soviet era, this vector has radically changed first towards representative ideological buildings, and in modern conditions – towards commercial multi-storey residential development. The purpose of the article was to trace how the waterway – the Dnieper River, accent landforms and landscaping influenced the formation of Kyiv during its existence, as well as to determine the features of the influence of these natural components on the modern development of the city. The scientific novelty of the study lies in a comprehensive coverage of the relationship between the natural components and development of Kyiv from ancient times to the present, identifying modern problems, their causes and ways to overcome them.